Magijska drugačnost junakinj Šeligove dramatike in proze - Toporišič, Tomaž (Slavia Centralis, 2020)
MAGICAL OTHERNESS OF THE HEROINES OF ŠELIGO’S PLAYS AND FICTIONThe essay deals with the topic of otherness in the plays and fiction of Rudi Šeligo (Kdor skak tisti hlap, Svatba, Lepa Vida, Čarovnica iz zgornje Davče, Ana in Volčji čas ljubezni; Triptih Agate Schwartzkobler). It focuses on its heroines and shows how the theme of otherness is not revealed and manifested through realistic tactics, but by using a specific procedure (Šeligo 1988a: 108) with which the author produces and thematically differentiates otherness by breaking down the hegemonic language and its logos (to put it in the words of Antonin Artaud), thus building up a version of magical theatre characterised by his specific, singular politics of prose, drama and theatre. Thus, Šeligo reveals the neuralgic points of today’s society, which, instead of opening legitimate channels for expressing conflicting and alternative opinions by consensus, closes the space for otherness, plurality, and abolishes the right to otherness at the ultimate level.
Keywords: otherness; magical theatre; heroines; contemporary Slovene drama; Antonin Artaud; authenticity